[NMe4][I4Br5]: A new Iodobromide from an Ionic Liquid with Halogen–Halogen Interactions. Issue 2 (25th November 2016) - Mann, Lisa; Voßnacker, Patrick; Müller, Carsten; Riedel, Sebastian
Abstract: Tetramethylammonium tetraiodopentabromide [NMe4 ][I4 Br5 ] was the first iodobromide to be synthesized and crystallized in an ionic liquid as well as in dichloromethane. The new iodobromides show different structure motives yet are unknown from other nonahalides and can be better described as [(I2 Br3 ) − ⋅2 IBr]. The additional IBr units are connected by halogen–halogen interactions on the central V‐shaped [I2 Br3 ] − . The characterization was performed by Raman spectroscopy and single crystal X‐ray structure determination. Conductivity measurements, thermogravimetric analysis and quantum‐chemical calculations completed the structural discussion. Abstract : Solvent‐dependent structure : The first synthesis and characterization of [NMe4 ][I4 Br5 ] in an ionic liquid as well in dichloromethane is reported. Both crystal structures show two halogen bonds and therefore differ from the so far known nonahalide structures. Quantum‐chemical calculations underpin this extraordinary binding situation.